Aktivitas Antioksidatif Pasta Kacang Tanah Sangrai - Nordiansyah Firahmi; Sutardi Sutardi; Haryadi Haryadi (agriTECH, 1998)
Antioxidative activity of peanut butter made from peanut roasted at various temperatures and times and at different level of peeling were studied. Dry fresh peanut of different level of peeling, Lei) whole, shelled d hulled samples were roasted at 150 , 160 , 170 , and 180 C for 30, 45, .60, and 75 min. The roasted samples were freed from the shell and hull and then ground to pass a 0.2 mm screen. The resulted peanut butters were characterized for their oxidative ittibition by incorporating them into oleic acid and kept at 60 C for 24, 48, and 72 hr, and then the peroxide values were followed. Lower peroxide value reflected higher antioxidative activity. The antioxidative activity was expressed as the ability of the butter to inhibit oxidation of oleic acid. Peroxide value of the kept oleic acid increased tremendously, while those of the mixtures of oleic and the butters made from peanut of various treatment after keeping for 24 hr showed no difference from each other. After kept for 48 hr the difference in peroxide value of the mixtures was again not found. Keeping for 72 hr resulted in significantly difference in the values. The butter made from roasted; shelled peanut showed higher antioxidative activity (62,62%) than that obtained from roasting of unshelled peanut did (62,22%). Excluding peanut hull in grinding roasted peanut to produce butter gave lower activity (62,27%) than grinding of roasted peanut along with the hull did (64,56%). Increase in temperature and roasting time resulted in increase in the activity. From the various temperature the highest antioxidative activity was shown by the butter made from peanut roasted at 180 C (64,90%) and the lowest value was resulted from the roasting at 150 C (61,46%). While from the various roasting times, the lowest activity was given by roasting of peanut for 75 min (67,03%) and the lowest value resulted from roasting for 30 min (58,43%)